Pelaksanaan Pendamping Penggunaan Buku Kesehatan Ibu Dan Anak (KIA) Terhadap Prilaku Ibu Dalam Pelayanan Kesehatan Selama Hamil, Puskesmas Gomo kec. Gomo Kab. Nias Selatan Tahun 2023 - Miswita Manao; Lisdayanti Simanjuntak; Dina Afriani; Mastaida Tambun; Dewi Sartika Hutabarat (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Menstrual cycle disorders are menstrual disorders, also known as abnormal uterine The maternal and child health program is one of the priorities of the Ministry of Health and the success of the MCH program is one of the main indicators in the National Long Term Development Plan (RPJPN) 2005 – 2025. The aim of implementing assistance in the use of maternal and child health books (KIA) on the behavior of pregnant women in services. Health During Pregnancy, Maternity and Postpartum in the Working Area of ​​the Gomo Health Center, Gomo District, South Nias Regency, 2023. Pre-Experimental Designs research method. The population in this study was all pregnant women at the Gomo District Health Center, Gomo District Health Center. South Nias in 2023 as many as 102 people. Wilcoxon Signed Ranks Test statistical test. The results of the Wilcoxon Signed Ranks Test showed a p value < 0.05. The results of the research were that the majority of pregnant women who had a positive attitude before the implementation of assistance (pre test) were 31 people (62.00%) after (post test) for four visits there was an increase There were 43 positive attitudes among pregnant women (86.00%). Then the results of the Wilcoxon statistical test obtained p (0.001) < 0.005, so it can be concluded that the null hypothesis was rejected, meaning that there was effectiveness in the actions of pregnant women after being accompanied by the KIA book compared to before being accompanied by the KIA book. Based on the results research, a way to find out early detection of the dangers of pregnancy at the nearest health service on a regular or periodic basis.